2017
DOI: 10.1187/cbe.17-03-0051
|View full text |Cite
|
Sign up to set email alerts
|

A Model for Postdoctoral Education That Promotes Minority and Majority Success in the Biomedical Sciences

Abstract: During science postdoctoral experiences, underrepresented minorities (URMs) disproportionately drop out, and models show interventions to increase URM scientists in academia could be most effective at this time. FIRST fellows, who are 50% URMs and 70% women, are as or more successful than a comparison group, due to their intentional community and explicit training in teaching.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 14 publications
(29 reference statements)
0
31
0
Order By: Relevance
“…However, within the qualitative findings, participant voices were often adequately represented. Only two qualitative studies clearly identified that ethical issues were addressed [42,52]. Quality assessment scores for quantitative studies and quantitative components of mixed method studies ranged from low (n � 12) to medium (n � 11), with no high quality quantitative studies identified ( Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, within the qualitative findings, participant voices were often adequately represented. Only two qualitative studies clearly identified that ethical issues were addressed [42,52]. Quality assessment scores for quantitative studies and quantitative components of mixed method studies ranged from low (n � 12) to medium (n � 11), with no high quality quantitative studies identified ( Supplementary Table S2).…”
Section: Resultsmentioning
confidence: 99%
“…A study about a structured postdoctoral program in the social sciences identified a statistically significant positive effect on postdocs' publication activity [35]. In a recent case study, the overall publication rate of postdocs who had intensive training in both research and teaching exceeded the rate for postdocs focused on research only [42]. Kuhn and Castano [48] reported participation in a mentorship program increased competency in grant writing and science communication.…”
Section: Writing and Publication Skillsmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, in this study, 38% reported having only one year of postdoctoral training or exposure to grant writing processes (75% had no experience), which is considered insufficient to obtain funding for research that will produce enough publications for future grants and career promotions. [17][18][19] Therefore, NRMN STAR's supplemental activities fills a significant training gap between being a graduate student to holding research career positions.…”
Section: Discussionmentioning
confidence: 99%